‘Origin Stories of the ‘Grants Uranium District’ in Northwestern New Mexico: Archives, Memoirs, and Exploratory Boreholes in the Production of Geological Regions - Thomas De Pree (Engaging Science, Technology, and Society)
The “Grants uranium district” of northwestern New Mexico yielded more uranium ore than any other mining district in the United States during the Cold War Period (1947-1989). After the national market for uranium collapsed in 1979, the mines were slowly abandoned and the mills were decommissioned. More than ninety-eight percent of what was mined remains on site as toxic mine wastes, overburden, and mill tailings—in a landscape fractured by underground mine workings, punctured by exploratory boreholes, and saturated with the liquid waste discharged from the uranium mines and mills. Designated as a national “sacrifice zone,” the former mining district constitutes egregious cases of environmental injustice and racism, as well as deeper impositions of settler colonialism. The former mining district overlaps multiple Native Nations and their broader ancestral homelands, as well as Nuevomexícano (“Hispano/Indo-Hispano”) land grant allottees, and rural white (“Anglo”) majority settler towns and communities. Returning to the origin stories of the mining district and the broader geological region, this article traces the epistemic production of the geophysical landscape by questioning the relationship between boreholes, geologic archives, and the memoir genre in geology. This style of historiography offers a critique of the historical background papers in geologic memoirs as one way of reading against the archival grain, and exposing the physical and material impacts of dispossession resulting from mineral exploration. Situated within anthropological traditions of science and technology studies and critical studies of settler colonialism, this article aims to contribute to emerging scholarship in “geological anthropology” and “political geology.”